COVID-19 Vaccination Status and Capsular Contracture Following Prosthetic Breast Reconstruction: A Retrospective, Multicenter Nested Case-Control Study. (17th November 2022) - Berger, Lauren E; Spoer, Daisy L; Bovill, John D; Huffman, Samuel S; Bell, Alice C; Truong, Brian N; Singh, Anusha; Fan, Kenneth L; Tom, Laura K
Abstract: Background: Capsular contracture (CC) is a common long-term complication following prosthetic-based breast reconstruction (PBBR). Seven cases of CC following mRNA vaccination for coronavirus 2019 (COVID-19) are reported in the literature. Objectives: The aim of this study was to determine whether receiving the COVID-19 vaccine was associated with CC development following PBBR. Methods: A retrospective, multicenter nested case-control study was performed from January 2014 to July 2022 of adult female patients who underwent PBBR with acellular dermal matrix placement. Cases of CC were selected if no adjuvant radiation was received and they presented for follow-up between December 2020 and July 2022. Controls included patients who met inclusion criteria but who did not experience CC in either breast. Patient demographics, breast cancer characteristics, reconstructive surgery details, postoperative complications, and COVID-19 exposure details were analyzed and correlated with CC development. Results: Of a total of 230 patients (393 breasts) who received PBBR, 85 patients (135 breasts) met inclusion criteria, of whom 12 patients (19 breasts) developed CC and 73 patients (116 breasts) did not. At the time of median follow-up of 18.1 months (n = 85; interquartile range, 12.2-33.6 months), no statistically significant differences were observed between the short- or long-term complications in cases or controls. There were no significant differences in COVID-19 vaccination status, number of vaccine doses, or vaccination type between cases and controls. Vaccination status was not associated with greater odds of CC development (odds ratio, 1.44; 95% CI, 0.42-5.37; P > .05). Conclusions: Direct association between CC and COVID-19 vaccination is difficult to prove. Given the known risk of severe COVID-19 infection among immunocompromised patients, those with breast cancer who undergo PBBR should be properly counseled on the benefits and risks of vaccination. Level of Evidence: 4: